1993
DOI: 10.1164/ajrccm/147.5.1144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrical Stimulation of the Hypoglossal Nerve on Airflow Mechanics in the Isolated Upper Airway

Abstract: To determine the influence of electrical hypoglossal (HG) nerve stimulation on upper airway airflow mechanics, we analyzed pressure-flow relationships obtained during bilateral supramaximal HG nerve stimulation over a range of frequencies from 0 to 100 Hz in the isolated feline upper airway. Inspiratory airflow (VI), hypopharyngeal pressure (Php), and pharyngeal pressure (Pph) immediately upstream from the flow-limiting site (FLS) were recorded while Php was rapidly lowered to achieve inspiratory flow limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
95
0
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 25 publications
11
95
0
3
Order By: Relevance
“…Based on the present experiments, whole XIIth nerve stimulation was most certainly associated with tongue retraction in the experiments of Schwartz et al (1993) and Hida et al (1995), indicating that improved pharyngeal mechanics and tongue retraction are somehow linked.…”
Section: Physiological Significancesupporting
confidence: 54%
See 1 more Smart Citation
“…Based on the present experiments, whole XIIth nerve stimulation was most certainly associated with tongue retraction in the experiments of Schwartz et al (1993) and Hida et al (1995), indicating that improved pharyngeal mechanics and tongue retraction are somehow linked.…”
Section: Physiological Significancesupporting
confidence: 54%
“…However, recent evidence from both animal models and human subjects shows that tongue muscle co-activation improves pharyngeal airway mechanics. Schwartz et al (1993) found that whole XIIth nerve stimulation increased the maximal rate of inspiratory flow and decreased collapsibility of the isolated feline upper airway. In a similar experiment (Hida et al 1995) it was shown that whole XIIth nerve stimulation decreased the compliance of the isolated canine upper airway from 4 to 3 ml cmHµO¢.…”
Section: Physiological Significancementioning
confidence: 92%
“…Although it is believed that these muscles act in unison, the genioglossus is the most easily measured. Selective activation of the genioglossus has been shown to reduce airway collapsibility in both humans (3) and animal models (17). During wakefulness, children with OSAS have an elevated EMGgg compared with normal control subjects (4), likely a product of negative airway pressure on laryngeal mucosal mechanoreceptors (5).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as Pcrit fell below a minimally negative threshold of approximately 25 cm H 2 O, sleep apnea remitted, suggesting that changes in Pcrit play a pivotal role in the pathogenesis of this disorder (see Figure 1, right) (25,(57)(58)(59)(60)(61). In further studies, investigators have demonstrated that Pcrit is determined by mechanical and neural factors that regulate pharyngeal collapsibility (62)(63)(64)(65)(66)(67). Investigators measuring airway collapsibility in the absence of neuromuscular activity have demonstrated small, but consistent elevations in Pcrit in patients with sleep apnea compared with normal subjects (68)(69)(70).…”
Section: Obesity and Upper Airway Neuromechanical Control Modeling Upmentioning
confidence: 95%